الإمالة - عوض, سامي; منصور, رائد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
تتمتع الصيغ اللغوية الحية المتفاعلة مع الحياة بالمرونة التي تجعلها قادرةً على أداء المعاني بسهولة ويسر وخفة وأقل قدر ممكن من الجهد العضلي. ويقف عامل الخفة وراء الكثير من الظواهر والتغيرات اللغوية في اللغة العربية مثل ظاهرة الإمالة. والإمالة ظاهرة صوتية سياقية يلجأ إليها الناطق طلباً للخفة واختصاراً للجهد العضلي، وهي أنواع أشهرها وأكثرها شيوعاً إمالة الفتح إلى الكسر أو الألف إلى الياء. وقد وقف الدرس اللغوي العربي القديم على حقيقة الإمالة عندما اعتبرها عملية تقريب بين الأصوات (الصائتة) لتحقيق الانسجام بينها، ووضع لها أسساً وقواعد تتعلق بالبنية الصوتية للكلمة مبيناً أنواعها وأسبابها والعوامل المؤثرة فيها مدركاً ارتباط الانسجام بين الأصوات بمواضع نطق تلك الأصوات، لأن التقريب بين الأصوات والانسجام بينها يؤدي إلى سهولة النطق وسرعته. والدرس الحديث اعتبر الإمالة ظاهرة من ظواهر المماثلة التي تقوم على تأثير صوت في صوت آخر ليصبح نطق المتأثر قريباً من نطق المؤثر ومماثلاً له، والتأثير في البنية الصوتية قد يحدث مع وجود مجموعة من الأصوات التي تفصل بين المؤثر والمتأثر، كإمالة الألف بتأثير كسرة العين في كلمة: عندها. Linguistic forms of live languages have the flexibility that enables them to convey the meaning easily, effortlessly and smoothly with the least possible muscular effort. The “smoothness” or “lightness” factor lies behind many linguistic phenomena and linguistic change in Arabic, such as the vocalic inflection phenomenon (or assimilation phenomenon) (i.e. to pronounce the fatĥah like an English a). The vocalic inflection (inflection of a fatĥah to a kasrah) is an environmental phonological phenomenon which the speaker resorts to seeking lightness or smoothness, thus minimizing muscular effort. The most famous kind of imalah is the assimilation (imalah) of fatĥah to a kasrah, or the inflection of the alif to the ya’. Ancient Arabic linguistics studied vocalic inflection considering it as an assimilation of sounds (vowels) in order to achieve concord between them. It founded the bases and rules of this phenomenon related to phonological structure of the word, showing its kinds, reasons, and the factors that affect it. It also realized the connection of the concord between sounds with the places of their articulation, because bringing sounds nearer and harmony among them lead to easiness and quickness of articulation of sounds. Modern linguistics considers vocalic inflection (imalah) an assimilation phenomenon which is the effect of one sound on another, so that the affected sound is uttered close and similar to the affecting sound. The influence on the phonological structure may take place in the presence of a group of sounds separating the affecting and affected sounds, such as the vocalic inflection (imalah) of the alif under the influence of the kasrah of a’yn in i’ndaha.